Employing Traditional Stories to Enhance Critical Thinking Skills of Junior High School Students - Nur Fauzia; Rahayu Kuswardani; Abdur Rosyid; Fithriyah Inda Nur Abida; Diana Budi Darma (Humanitatis : Journal of Language and Literature, 2023)
In contemporary education, there is a growing interest in exploring alternative methods to cultivate critical thinking skills among junior high school students. Traditional stories, with their cultural richness and narrative depth, present an intriguing opportunity as a potential learning tool to foster such skills. This research aims to investigate the efficacy of utilizing traditional stories as a pedagogical instrument to enhance critical thinking abilities among junior high school students. By employing a qualitative research design, the study seeks to delve into the impact of traditional stories on students' critical thinking development. Adopting a qualitative research design, this study takes on a single case study approach, focusing on thirty eighth-grade students from SMPN 14. The participants were selected through a purposive sampling method. The research spans a duration of six weeks, during which carefully selected traditional stories were utilized as a medium for nurturing critical thinking experiences. Research instruments encompassed observation, interviews, and the implementation of specifically designed critical thinking worksheets. Data analysis was conducted using categorization and thematic processes to discern the patterns of change in the students' critical thinking capacities throughout the intervention. The findings of the research indicate that the incorporation of traditional stories effectively enhances the critical thinking skills of junior high school students. Throughout the learning process, students exhibited advancements in various facets of critical thinking, including problem identification, critical analysis, argument assessment, and reflective thinking. The critical thinking experiences derived from the utilization of traditional stories were instrumental in fostering deeper and contextually relevant thinking skills. As a result, the study recommends that educators consider integrating traditional stories into their teaching practices to facilitate the development of critical thinking abilities across different educational levels.